Biochemistry Laboratory Modern Theory and Tecniques - Boyer, Rodney (PEARSON, 2012)
This title covers the theories, techniques, and methodologies practiced in the biochemistry teaching and research lab. Instead of specific experiments, it focuses on detailed descriptions of modern techniques in experimental biochemistry and discusses the theory behind such techniques in detail.